Exploring the Effects of Text Length and Difficulty on RSVP Reading. (September 2016) - Hester, Michelle; Werner, Steffen; Greenwald, Cassie; Gunning, Jessica
Recent marketing efforts claim that by removing saccades, well designed Rapid Serial Visual Presentation (RSVP) text displays can increase reading speed without an overall loss of comprehension. Due to the cognitive load when displaying long text it has been suggested that RSVP is better utilized in shorter text or longer text presented in small sections. With the introduction of smart watches as display mediums, opportunities for these types of text display have become more prominent due to their small form-factor. These small screen displays have limited space and often are used to convey short messages, which have motivated a closer look at RSVP. In the current study, we investigate the effects of text length and text reading level on comprehension. We compare RSVP to traditional (left-to-right) text presentations. In line with previous studies our results show that there were no differences between comprehension for RSVP and traditional text displays at normal reading speeds. Future, research may focus on the effects of training and familiarity with RSVP and its performance at the marketed higher readings speeds.